Saúde e educação : uma análise de impacto utilizando Propensity Score Matching - Rocha, Maria Estela Basilio de Oliveira (2021)
This work estimated the effect of the School Health Program (PSE) on total failure, dropout and total age-grade distortion rates based on microdata from the School Census and Educational Indicators published by the National Institute of Educational Studies and Research Anísio Teixeira ( INEP) and in the list of public schools agreed in 2017 to the PSE provided by the Ministry of Education (MEC). The Propensity Score Matching method was used, applying sensitivity analyzes proposed by Ichino et al. (2008) and Oster (2017) and heterogeneous response tests in order to deepen issues intrinsic to the theme. The results showed that there is a reduction in failure rates, dropout rates and total age-grade distortion in schools agreed to the PSE when compared to non-agreed schools. Such effects are significant and stand out with greater intensity in the total failure rate. Furthermore, it was noted that the magnitude of the impact of the PSE is greater in the early years of elementary school (1st to 5th grade) when compared to the final years (6th to 9th grade). The sensitivity analyzes proposed by Ichino et al. (2008), and Oster (2017), indicated robustness in the results. The heterogeneous response tests, applied considering sample subgroups of teacher characteristics, class characteristics and socioeconomic level of the school, indicated a reduction in the analyzed rates, reinforcing the main result. In this context, there is confirmation of the hypothesis that schools agreed with PSE present a reduction in the total failure rate, total dropout rate and total age-grade distortion rate.